2015
DOI: 10.1074/jbc.m115.648345
|View full text |Cite
|
Sign up to set email alerts
|

Modulator of Apoptosis 1 (MOAP-1) Is a Tumor Suppressor Protein Linked to the RASSF1A Protein

Abstract: Background: MOAP-1 is a pro-apoptotic protein.Results: MOAP-1 expression is reduced in cancers and high expression correlated with increased patient survival. MOAP-1 can associate with tubulin and modulate tubulin stability. Furthermore, loss of the BH3 domain of MOAP-1 resulted in lack of tumor suppressor function.Conclusion: MOAP-1 is a highly regulated tumor suppressor protein.Significance: The loss of MOAP-1 may significantly contribute to tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 57 publications
0
35
0
1
Order By: Relevance
“…MOAP-1 is a regulator of the apoptotic executor Bax [48] and has tumor suppressor properties [49]. Activated Ras enhances the interaction between RASSF1A and MOAP-1 and this leads to Bax activation [46], translocation to mitochondria and apoptosis [47].…”
Section: Rassf1mentioning
confidence: 99%
See 1 more Smart Citation
“…MOAP-1 is a regulator of the apoptotic executor Bax [48] and has tumor suppressor properties [49]. Activated Ras enhances the interaction between RASSF1A and MOAP-1 and this leads to Bax activation [46], translocation to mitochondria and apoptosis [47].…”
Section: Rassf1mentioning
confidence: 99%
“…This is a Bax activating event. This whole process may involve positive feedback loops, as over-expression of MOAP-1 leads to upregulation of MST1 [49]. …”
Section: Rassf1mentioning
confidence: 99%
“…The two validated targets of miR-1228 identified using the miRTargetLink database might have important relevance in colorectal cancer ( Figure 4E). The first gene, MOAP1, has been previously identified as an important tumor suppressor molecule linked to the RASSF1A protein, with implications in apoptosis [41]. Data from The Human Protein Atlas [42] reveal that this protein is actually downregulated in colorectal cancer patients; the fact is that, in some instances, this can be contradictable with miR-1228-3p expression (which is also downregulated in tumor tissue).…”
Section: Discussionmentioning
confidence: 99%
“…LCE1F protein interacts with protein arginine methyltransferase 5 (PRMT5) in response to DNA damage [10]. MOAP1 participates in the internal and external pathways of cell death and activates the apoptotic protein BAX of Bcl-2 family [25]. Studies have shown that knockout of EIF3D significantly induces G2/M arrest and apoptosis by down-regulating cyclin B1 and upregulating p21 [26].…”
Section: Discussionmentioning
confidence: 99%
“…(a) 15 genes such as apoptotic regulator 1 (MOAP1) and eukaryotic translation initiation factor 3 subunit D (EIF3D) that were reported to regulate cell cycle, apoptosis, and cell death [25,26]. USP17L6P had a positive regulation relationship with TP53-regulated inhibitor of apoptosis (TRIAP1) that was associated with apoptosis and cell death [27].…”
Section: Coexpression Networkmentioning
confidence: 99%